Fluorescent periodic mesoporous organosilica nanoparticles dual-functionalized via click chemistry for two-photon photodynamic therapy in cells. Issue 33 (5th August 2016) - Croissant, Jonas G.; Picard, Sébastien; Aggad, Dina; Klausen, Maxime; Mauriello Jimenez, Chiara; Maynadier, Marie; Mongin, Olivier; Clermont, Guillaume; Genin, Emilie; Cattoën, Xavier; Wong Chi Man, Michel; Raehm, Laurence; et al.
Abstract : The synthesis of ethenylene-based periodic mesoporous organosilica nanoparticles for two-photon imaging and photodynamic therapy of breast cancer cells is described. Abstract : The synthesis of ethenylene-based periodic mesoporous organosilica nanoparticles for two-photon imaging and photodynamic therapy of breast cancer cells is described. A dedicated two-photon absorbing fluorophore possessing four triethoxysilyl groups and having large two-photon absorption in the near IR region, and azidopropyltriethoxysilane were incorporated into the structure. The mesoporous nanoparticles of 100 nm diameter were further functionalized by means of click chemistry with a propargylated fluorescent bromo-quinoline photosensitizer able to generate singlet oxygen. The photophysical properties and two-photon absorption properties of the nanoparticles were investigated evidencing complementary contribution of the two dyes. Both dyes contribute to the two-photon absorption response of the mesoporous nanoparticles while efficient FRET from the two-photon fluorophore to the quinoline sensitizer is observed. The dual-functionalized nanoparticles were incubated with MCF-7 breast cancer cells. Two-photon confocal imaging demonstrated the endocytosis of the nanoparticles within cancer cells. Moreover, brief two-photon irradiation (3 scans of 1.57 s) at 760 nm at high laser power (3 W) was shown to induce 40% of cancer cell death demonstrating the potential of the dual-functionalized mesoporous organosilica nanoparticles for two-photon photodynamic therapy.